2022
DOI: 10.1364/oe.470970
|View full text |Cite
|
Sign up to set email alerts
|

Real-time in-situ optical detection of fluid viscosity based on the Beer-Lambert law and machine learning

Abstract: As an important physical quantity to describe the resistance of fluid to flow, viscosity is an essential property of fluids in fluid mechanics, chemistry, medicine, as well as hydraulic engineering. While traditional measurement methods, including the rotating-cylinder method, capillary tube method and falling sphere method, have significant drawbacks especially in terms of accuracy, response time and the sample must be made to move. In this work, a novel Beer-Lambert law-based method was proposed for the visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…On the one hand, we discuss the impact of improving the accuracy of the sensor for the detection of methane gas concentration. Absorption properties follow the Beer–Lambert law [ 14 , 15 ]: …”
Section: Design Of Sensitive Element and Measurement Circuitmentioning
confidence: 99%
“…On the one hand, we discuss the impact of improving the accuracy of the sensor for the detection of methane gas concentration. Absorption properties follow the Beer–Lambert law [ 14 , 15 ]: …”
Section: Design Of Sensitive Element and Measurement Circuitmentioning
confidence: 99%
“…In the follow-up phase of the spectrum analysis to the data for 4 channels, it can be found that spectrum pecks were concentrated between 4-5Hz (Figs [12][13][14][15], Indicating that he characteristic frequency band was in this band. As well, the spectrum peaks of detection channels 1 and 2 decreased as the increase of concentration of combustible gas (Figs 14 and 15), and that of the two reference channels remained the same all the time (Figs 14 and 15).…”
Section: Plos Onementioning
confidence: 99%
“…On the one hand, discuss the impact of improving the accuracy of the sensor for the detection of combustible gas concentration. Absorption properties follow the Beer-Lambert law [ 14 , 15 ]: …”
Section: Design Of Sensitive Element and Measurement Circuitmentioning
confidence: 99%